The use of AI tools and their impact on the assessment of postgraduate courses in the technological field - Susana Hernando-Castro; Juan Diego López-Arquillo; Martín Perea-Álvarez-de-Eulate (Advances in Building Education)
This study analyzes the impact of using freely accessible generative AI in the evaluation of students in the Master's Program in Renewable Energies at Universidad Europea de Canarias, with the aim of proposing strategies to ensure that students maintain the necessary knowledge and technical skills. The case study focused on the "Renewable Energy Startups" module, worth 6 ECTS, where students completed practical activities with the assistance of AI tools. The evaluation of AI-generated results was conducted using the same rubric applied in a previous edition, when these tools were not yet available. Additionally, the AI-generated responses to exam questions based on the official syllabus were analyzed, and the time spent was compared with the minimum times outlined in the university's study plan. The findings show that, while AI can reduce the time needed to complete tasks, it is essential to redesign activities to integrate AI in an ethical and effective way. When approached correctly, AI can become a tool that enhances learning, improving students' technical skills without compromising the depth of knowledge.